2004
DOI: 10.1002/elps.200405932
|View full text |Cite
|
Sign up to set email alerts
|

Chiral capillary electrophoresis: Facts and fiction on the reproducibility of resolution with randomly substituted cyclodextrins

Abstract: Comparative enantioseparation of the enantiomers of 1,1'-binaphthyl-2,2'-diyl hydrogen phosphate was performed with cyclodextrin (CD)-modified capillary electrophoresis (CE). Two single isomers, beta-CD, heptakis(2,3,6-tri-O-methyl)-beta-CD (TM-beta-CD), and heptakis(2,6-di-O-methyl)-beta-CD (DM-beta-CD) of 98% purity as well as heptakis(2,3-di-O-acetyl)-beta-CD were used and compared in terms of resolution power to randomly methylated and corresponding acetylated beta-CDs, which were synthesized in our labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…However, when it comes to the quantification of the ratio of two isomers or the determination of the enantiomeric excess [36,37], a validation of the method has to be performed. In this case, care must be taken if randomly substituted CD derivatives were employed [38]. As has been demonstrated by the intercompany crossvalidation exercise on clenbuterol [7], CD-modified CE has a much higher separation power and robustness than chiral HPLC and should be therefore used without any reservation.…”
Section: Chiral Analysismentioning
confidence: 98%
“…However, when it comes to the quantification of the ratio of two isomers or the determination of the enantiomeric excess [36,37], a validation of the method has to be performed. In this case, care must be taken if randomly substituted CD derivatives were employed [38]. As has been demonstrated by the intercompany crossvalidation exercise on clenbuterol [7], CD-modified CE has a much higher separation power and robustness than chiral HPLC and should be therefore used without any reservation.…”
Section: Chiral Analysismentioning
confidence: 98%
“…Characterization of these CDs indicated relatively good homogeneity in terms of degree of sulfation. Elemental analysis of the highly S-a-CD, highly S-b-CD, and highly S-g-CD showed that the average sulfate contents were 11, 12, and 13 per CD molecule, respectively [22], even if heterogeneity in terms of position of substitution has been proved for similar substituted CDs [23]. The molar concentration unit is used to permit the comparison of the different selectors used and the calculation of apparent and averaged binding constants.…”
Section: Chemicalsmentioning
confidence: 99%
“…Inclusion within the CD cavity is responsible for chiral discrimination [20]; CD varieties that are neutral (native or derivatized), positively charged, and negatively charged are commercially available. More recently, the trend has been to create single-isomer derivatized CDs in an attempt to reduce batch-to-batch variability and improve reproducibility [21]. Other chiral selectors include [5,22]: proteins [23,24], crown ethers [25], oligosaccharides, polysaccharides, macrocyclic antibiotics [26], and surfactant aggregates [27,28] (micelles (monomeric [29,30] and polymeric [31][32][33][34]), vesicles [35,36], and microemulsions (vide infra)).…”
Section: Introductionmentioning
confidence: 99%